Mechanical properties, hemocompatibility, cytotoxicity and systemic toxicity of carbon fibers/poly(ether-ether-ketone) composites with different fiber lengths as orthopedic implants. Issue 18 (12th December 2019) - Li, Ying; Wang, Dalin; Qin, Wen; Jia, Hui; Wu, Yang; Ma, Jing; Tang, Bin
Abstract: Poly(ether-ether-ketone) (PEEK) has attracted more and more attention due to its chemical resistance, biocompatibility and other properties. Furthermore, carbon fibers-PEEK composite (CF-PEEK) has been considered as a novel implant because of its high mechanical strength and elastic modulus that matching with human bones. However, the length of CF has a great influence on mechanical strength and elastic modulus of the randomly distributed chopped CF-PEEK composites. In this work, CF-PEEK composites with more than 10 times length difference of fibers (length of short CF: 150–200 μm and length of long CF: 2–3 mm) were studied. As the results shown, the mechanical strength (including tensile strength, bending strength and compressive strength) of long CF-PEEK composites were more than two times of that of short CF-PEEK composites. Meanwhile, tensile modulus and bending modulus of the two kinds of composites matched well with the modulus of human cortical bone. In addition, according to the results of cytotoxicity test and hemocompatibility assessment, it indicated that the two kinds of CF-PEEK composites showed mild toxicity and no hemolytic reaction. And the histopathological section of systemic toxicity test showed that the CF-PEEK composites had no obvious acute toxicity to organisms.